Presacral tumors: a retrospective analysis of 112 cases with emphasis on diagnostic challenges and surgical outcomes - Chen, Shi; Deng, Heng; Li, Ming; Fang, Xiaoli (Frontiers in Surgery, 2025)
BackgroundPresacral tumors are rare entities with heterogeneous pathology including malignant potential. Due to nonspecific symptoms mimicking common anorectal diseases, misdiagnosis remains a major challenge that may delay treatment and worsen prognosis, particularly for malignant variants. This study analyzes diagnostic pitfalls and surgical outcomes in a large single-center cohort.MethodsWe retrospectively reviewed 112 presacral tumor cases treated at our tertiary colorectal center (2015–2025). Data included demographics, clinical presentation, misdiagnosis rates, imaging accuracy, surgical approaches, and complications. Statistical analysis utilized descriptive methods and Chi-square tests.ResultsAmong 112 patients (male 62, female 50; median age 52 years, range 18–93), 57% presented with anal/rectal pain, while 20.5% were asymptomatic. 85.7% of patients were referred from non-specialized centers. Misdiagnosis occurred in 29.5% (predominantly as anal fistula/abscess or pilonidal sinus). Preoperative imaging (MRI/CT) correctly diagnosed 60% of tumors >3 cm vs. 21.2% of smaller tumors (P < 0.001). Surgical approaches: 93.8% underwent transsacral/transanal resection, 6.2% required laparoscopic/combined abdominoperineal resection. Major complications (Clavien-Dindo grade III) occurred in 4.5% of patients (n = 5/112), including hemorrhage, rectal injury, and sacral nerve injury. No mortality occurred. Pathology revealed 11.6% malignancy risk.ConclusionHigh misdiagnosis rates (29.5%) data support for heightened suspicion in patients with “refractory perianal sepsis”, especially given the potential for malignancy. MRI showed significantly higher diagnostic accuracy for tumors >3 cm. Transsacral/transanal resection is safe and effective for most cases (93.8%), with low major morbidity. Centralized management in specialized centers optimizes outcomes.